Applying ERRC of Blue Ocean Strategy: A Value Innovation for Contracting Carrier Company Study Case in Indonesia - Sugiono, Ahmad; Rahayu, Agus; Wibowo, Lili Adi (Journal of Governance Risk Management Compliance and Sustainability, 2021)
This study aims to determine the strategy's ability to make price competition irrelevant and optimize the company's operating costs. This type of research uses descriptive qualitative research with the subject of this research is one of the Freight Forwarding companies in Jakarta, namely IGL. The results obtained in this study, among others, by creating partners abroad (Key Partnership), which focus on having freehand shipments import and nominee shipments export, can make a condition where price competition becomes irrelevant. The results also show that focusing on being a contractual carrier and procurement of warehouses is also proven to positively impact operational costs and company performance, provide added value to customers, and support the company's main business.